PENDEKATAN ENGAGEMENT DALAM MEMBANGUN KINERJA PEGAWAI - Astrid Yuniar Nurbaity; Heru Sulistyo (Jurnal Ekonomi dan Bisnis, 2013)
The research was conducted on Kesbangpol dan Linmas Kota Salatiga with the aim to determine the effect of Quality of Work Life and Employee Engagement on Employee Performance. The research data obtained through questionnaires to 63 respondents who are employees of Kesbangpol dan Linmas Kota Salatiga using census. The results of the data obtained is processed using Partial Least Square (PLS) with PLS Smart Program. The results show that quality of working life contributing positively and significantly to Employee Engagement and Employee Performance, also Employee Engagement contribute positively and significantly to Employee Performance.Keyword: Quality of Work Life, Employee Engagement , Employee Performance